Begonia langenbergiana (Begoniaceae) a new species from the south of São Paulo State, Brazil - Kollmann, Ludovic Jean Charles (Phytotaxa, 2018)
Begonia langenbergiana, a new species of Begonia from São Paulo State, Brazil is described. Begonia langenbergiana is morphologically similar to Begonia itaguassuensis with which it is compared. The new species grows in hygrophilous Atlantic Forest in the south of São Paulo State, Brazil. A description, comparisons with morphologically similar species, etymology, taxonomic comments, illustrations, a map and the conservation status of the new species are provided.